PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI SEBAGAI VARIABEL INTERVENING PADA PT. STARLIFT INDONESIA 88 - Saman, Muhammad; Nuraeni, Nuraeni; Hasanah, Hasanah (JURNAL MUHAMMADIYAH MANAJEMEN BISNIS, 2024)
ABSTRACTThe purpose of this study was conducted to determine and analyze the influence of leadership, work environment and motivation on employee performance at PT. Starlift Indonesia 88 which consists of Leadership, Work Environment and Motivation. The population in this study are employees of PT. Starlift Indonesia 88 with a total sample of 133 people. The method of collecting data in this study is a questionnaire and documentation. The data analysis method in this study used the Structural Equation Modeling (SEM) method and the analytical tool used in this method was the Smart-PLS software.From the results of testing the hypothesis by measuring the Outer model and Inner Model it is stated that leadership has a significant effect on motivation, work environment has a significant effect on motivation, leadership has a significant effect on employee performance, work environment has no significant effect on employee performance, employee motivation has no significant effect on employee performance , leadership through work motivation has no significant effect on employee performance, and the work environment through work motivation has no significant effect on employee performance. Keywords: leadership, environmental, motivation